2017
DOI: 10.19082/5525
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Gerkin, Queen's College, George, and Jackson methods in estimating maximal oxygen consumption

Abstract: Background and aimTest of maximal oxygen consumption is the gold standard for measuring cardio-pulmonary fitness. This study aimed to determine correlation of Gerkin, Queen’s College, George, and Jackson methods in estimating maximal oxygen consumption, and demographic factors affecting maximal oxygen consumption.MethodsThis descriptive cross-sectional study was conducted in a census of medical emergency students (n=57) in Qazvin University of Medical Sciences in 2016. The subjects firstly completed the Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…The results indicated that participants with higher body fat percentages were still able to complete the 60 s forearm plank. Our findings are contrary to previous research indicating a correlation between obesity and lower forearm plank times in the general population [23]. This divergence is likely attributed to the elevated levels of muscular strength observed, especially among younger participants.…”
Section: Muscular Strength and Endurancecontrasting
confidence: 99%
See 2 more Smart Citations
“…The results indicated that participants with higher body fat percentages were still able to complete the 60 s forearm plank. Our findings are contrary to previous research indicating a correlation between obesity and lower forearm plank times in the general population [23]. This divergence is likely attributed to the elevated levels of muscular strength observed, especially among younger participants.…”
Section: Muscular Strength and Endurancecontrasting
confidence: 99%
“…The participants chose one of three submaximal (graded) cardiovascular test (GXT) options: the Gerkin treadmill test, the YMCA cycle ergometer test, or the Queen's College step test [21,23]. The majority of the officers chose to complete the Gerkin treadmill test (60/83; 72.3%).…”
Section: Cardiovascular Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A study investigated the accuracy of the non-exercise estimation of the VO2max method compared to the cooper 12 min test, and reported moderate to high reliability/specificity (71.5%) in firefighters [ 52 ]. Another study reported that moderate to moderate correlations existed between non-exercise estimation of VO2max and the Gerkin treadmill test (r = 0.69) and the Queen’s College step test (r = 0.51) [ 53 ]. The results in the current study indicated that 47.2% of firefighters did not meet the minimum requirement of 42 mL·kg·min for firefighting, as recommended by many researchers.…”
Section: Discussionmentioning
confidence: 99%